Performance of joint Iterative detection and decoding in coherent optical channels - Castrillon, Mario A. (2015)
Fil: Castrillon, Mario A. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.